ETIKA SAMIN: SUATU KAJIAN FILSAFAT NUSANTARA - Syahrul Kirom (Jurnal Filsafat "WISDOM", 2012)
Negative images of Samin community until now is still felt by a small community in Central Java. This is not completely true because the people of Samin also has ethical values in their life. This study is a library research, with the moral values of Samin community as material object and ethics as formal object. The purpose of this study was to explore the ethics of Samin community. The results of this study confirm that there are two ethics in the local wisdom of Samin community, namely theological and deontological ethics. Theological ethics rooted in the book of the Religion of Adam Jamus Kalimasada, associated with nobleness of soul and character. Deontological ethics, as obligations contained in the teachings of Samin, such as: aja srei drengki, tukar padu, dahpen kemeren, and mbadhog colong. This principles are categorically imperative which must be implemented in daily life that also affect the harmony of the universe.